Serum and brain metabolomic study reveals the protective effects of Bai-Mi-Decoction on rats with ischemic stroke - Yang, Lingling; Su, Xiaojuan; Lu, Fangfang; Zong, Rong; Ding, Shuqin; Liu, Jing; Wilson, Gidion; Li, Liuyan; Yang, Youyue; Wang, Weibiao; Wang, Xiaoying; Chen, Jianyu; et al. (Frontiers in Pharmacology, 2022)
Bai Mi Decoction (BMD), which is composed of Eugenia caryophyllata, Myristica fragrans, Moschus berezovskii and Crocus sativu, is a characteristic TCM multi-herb formula for brain disease. However, the mechanism of protective effects of BMD on ischemic stroke (IS) still has not been clarified. Our study is designed to elucidate the protective effects and underlying mechanisms of BMD on IS by employing pharmacodynamics and serum and brain metabolomics methods. Now, ninety adult male Sprague-Dawley rats were randomly divided into the sham operation group (SHAM, vehicle), middle cerebral artery occlusion-reperfusion injury model group (MCAO/R, vehicle), positive control group (NMDP, 36 mg/kg/day nimodipine), low (BMDL, 0.805 g/kg/day), moderate (BMDM, 1.61 g/kg/day) and high (BMDH, 3.22 g/kg/day) dosage of BMD prophylactic administration groups. The drugs were dissolved in 0.5% CMC-Na and orally administered to rats with equal volume (100 g/ml body-weight) once a day for 14 consecutive days. Neurological deficit score, cerebral infarct volume, change in body weight, serum NO, SOD, MDA, GSH, GSSG levels were determined. Pathological abnormalities such as hematoxylin and eosin staining, the expressions of VEGF, caspase-3 and NF-κB were analyzed. Furthermore, serum and brain metabolic profiles were explored to reveal the underlying mechanism by UHPLC-QTOF-MS/MS technology. BMD exhibited significant neuroprotective effects on MCAO/R rats. As compared to MCAO/R model group, it could reduce the neurological deficit score and cerebral infarct volume, increase body weight, enhance GSH, SOD and GSSG activities, decrease NO and MDA contents of MCAO/R rats. Meanwhile, BMD could ameliorate pathological abnormalities of MCAO/R rats through reducing neuronal loss, vacuolated spaces, shrunken neurons and destructed neuron structure, as well as regulating the expressions of VEGF, caspase-3 and NF-κB. UHPLC-QTOF-MS/MS based serum and brain metabolomics analysis found a total of 53 differential metabolites between MCAO/R and SHAM groups, 30 of which were significantly regulated by BMD intervention; and further metabolic pathway analysis implied the protective effects were mainly associated with amino acid and glycerophospholipid metabolisms. Our pharmacodynamics and metabolomics results revealed the neuroprotective effects of BMD on MCAO/R rats, and the underlying mechanisms were probably related to amino acid and glycerophospholipid metabolisms.